On Volatility Transmission from Crude Oil to Agricultural Commodities - Kumar, Dilip (Scientific Research, 2017)
The paper examines volatility transmission from crude oil market to agricultural commodities like wheat, corn, cotton and soybeans. We find that the volatility transmission from crude oil to agricultural commodities exhibits sudden changes over a study period. We also examine whether the sudden changes in volatility influence the observed sudden changes in volatility transmission from crude oil to agricultural commodities. Our results indicate the observed sudden change in volatility transmission mechanism is not influenced by sudden changes in volatility series.
Keywords: Volatility Spillover; Crude Oil; Agricultural Commodities; Volatility Estimator; Sudden Changes